The right to health as a condition for entry and a limit to the removal of a migrant (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The essay analyzes the relationship between migration and health, investigating the cases of protection for health reasons or the issue of a resident permit for the entry and residence on Italian territory. The work also examines the limit for the removal of a migrant due to health reason, also in the framework of the case law of the European Court of Human Rights and of the Court of Justice of the European Union. From a methodological point of view, the essay combines regulatory and jurisprudential analysis with the examination of data relating to the residence permits for medical treatment, obtained through a generalized civic access, in order to understand the impact of the reforms adopted in the recent years on the health of foreigners and in particular the number and nationalities of those who have been authorized to remain in the territory for health reasons.
Keywords: Health; migration; asylum; protection; return